2022
DOI: 10.3389/fcimb.2022.864479
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiota-Driven Cell Migration in Carcinogenesis and Metastasis

Abstract: The oral cavity harbors approximately 1,000 microbial species, and both pathogenic and commensal strains are involved in the development of carcinogenesis by stimulating chronic inflammation, affecting cell proliferation, and inhibiting cell apoptosis. Moreover, some substances produced by oral bacteria can also act in a carcinogenic manner. The link between oral microbiota and chronic inflammation as well as cell proliferation has been well established. Recently, increasing evidence has indicated the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 149 publications
(179 reference statements)
0
6
0
Order By: Relevance
“…Some have proposed that the association between periodontitis and the risk of different types of cancer is due to the chronic inflammation caused by periodontitis, which drives cancer development by infiltration of leukocytes in the tumor microenvironment ( Hanke et al, 1990 ; Garrett, 2015 ). Numerous studies have indeed reported a relationship between periodontal disease and various types of cancer ( Aas et al, 2005 ; Keijser et al, 2008 ; Bik et al, 2010 ; Segata et al, 2011 ; Soder et al, 2011 , 2021 ; Norder Grusell et al, 2013 ; Dong et al, 2018 ; Bai et al, 2022 ). In addition, studies have also shown that the oral microbiota may contribute to carcinogenesis by altering the homeostasis/cellular metabolism, the immune responses creating a proinflammatory microenvironment, cell migration and production of carcinogenic metabolites ( Garrett, 2015 ; Bai et al, 2022 ; Lamont et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some have proposed that the association between periodontitis and the risk of different types of cancer is due to the chronic inflammation caused by periodontitis, which drives cancer development by infiltration of leukocytes in the tumor microenvironment ( Hanke et al, 1990 ; Garrett, 2015 ). Numerous studies have indeed reported a relationship between periodontal disease and various types of cancer ( Aas et al, 2005 ; Keijser et al, 2008 ; Bik et al, 2010 ; Segata et al, 2011 ; Soder et al, 2011 , 2021 ; Norder Grusell et al, 2013 ; Dong et al, 2018 ; Bai et al, 2022 ). In addition, studies have also shown that the oral microbiota may contribute to carcinogenesis by altering the homeostasis/cellular metabolism, the immune responses creating a proinflammatory microenvironment, cell migration and production of carcinogenic metabolites ( Garrett, 2015 ; Bai et al, 2022 ; Lamont et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…ATG was also often used to treat severe aplastic anemia and altered patients' salivary microbiota but did not lead to a clear change in diversity over time (Ames et al, 2019 ). Similarly, RTRs were also all treated with FK506 and MMF which were related to oral cancer (Li et al, 2021 ) or oral ulcer (Asare and Gatzke, 2020 ), and these oral diseases were also related to salivary floras (Lin et al, 2021 ; Bai et al, 2022 ). Not only salivary microbiota but these immunosuppressants had been linked to the altered intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Oral microbiota is a major risk factor for OSCC. Associated interactions between oral microorganisms and host can promote the progression of OSCC ( Bai et al., 2022 ). In this study, we identified 652 upregulated and 1,047 downregulated genes in the OSCC tissues based on the GSE140707 dataset, as well as 162 upregulated and 118 downregulated genes in the GSE138216 dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Oral microbiota is a major risk factor for OSCC. Associated interactions between oral microorganisms and host can promote the progression of OSCC (Bai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%